2022
DOI: 10.3390/world3040050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Corporate Governance, Organisational Resilience and Sustainable Practices Developed by Brazilian Companies during the COVID-19 Pandemic: An Exploratory Study

Abstract: This paper aims to present aspects related to corporate governance, organisational resilience and sustainable practices developed by Brazilian companies during the COVID-19 pandemic. The methodological strategy included documentary research to identify sustainability reports published by companies listed on the Ibovespa index, which were examined through the content analysis technique. The results allowed light to be shed on opportunities for improvement concerning sustainability and corporate governance. Rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Aligning with the previous research, our study also found that strong corporate governance, reflected in higher governance rankings, was associated with greater adoption of online occupational health measures, including online occupational health services (RR = 2.03) and mental health promotion activities (RR = 2.01) during the evolution of teleworking. Corporate governance is pivotal in shaping a company’s approach to telework, emphasizing strategic decision-making, business continuity, employee well-being, and societal compliance [ 17 , 54 ]. Research also indicates that companies with engaged boards and management exhibit better occupational safety and health performance [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aligning with the previous research, our study also found that strong corporate governance, reflected in higher governance rankings, was associated with greater adoption of online occupational health measures, including online occupational health services (RR = 2.03) and mental health promotion activities (RR = 2.01) during the evolution of teleworking. Corporate governance is pivotal in shaping a company’s approach to telework, emphasizing strategic decision-making, business continuity, employee well-being, and societal compliance [ 17 , 54 ]. Research also indicates that companies with engaged boards and management exhibit better occupational safety and health performance [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%